E-COMMERCE PADA TOKO IT SOLUTION JAMBI BERBASIS MOBILE - Astuti , Reny; Kusaini, Maulana; -, Pariyadi (JURNAL AKADEMIKA, 2023)
E-Commerce is an online buying and selling system that connects companies or sellers to consumers in the form of electronic transactions. In line with the rapid development of the technology sector, companies belonging to small, medium and large industries, which are one of the many actors and supporters of economic activity in this country, are increasingly being encouraged to use advanced technology as a weapon to survive and win. Competition is getting tougher and tougher every day. IT Solution Jambi is a business entity engaged in providing services and selling computers. E-commerce at the Jambi IT Solution Store is an online comp uter sales media application so that it is better known by the wider community, especially in the city of Jambi. This application is designed using Visual Studio Code tools, Firebase Database, React Native and React JS programming languages. The result of making this application is that it can provide convenience to customers in obtaining services and information about the services available in IT Solutions. It also makes it easy for business owners to manage all transactions made and in making more detailed reports.